(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Forensic taphonomy involves the use of decomposition to estimate post-mortem interval (PMI) or locate cadaveric grave. The process associated with carcass decomposition in outdoor setting. Some other methods are available to determine the accurate post mortem interval (PMI). Instead of these methods, a soil-based approach one of the best methods to determine post mortem interval. As a consequence, we investigated the physical characteristics of the carcass, soil pH, soil moisture content, electrical conductivity and the concentration of total carbon, total nitrogen and soil-extractable phosphorus in soil beneath rabbit (Oryctolagus cuniculus L.) carcass which was placed on soil surface up to skeletal stage of decomposition. The significant increases were observed in concentration of soil pH, moisture content, soil-extractable phosphorus and total carbon.